2017
DOI: 10.1103/physrevd.95.022001
|View full text |Cite
|
Sign up to set email alerts
|

Audio-band coating thermal noise measurement for Advanced LIGO with a multimode optical resonator

Abstract: In modern high precision optical instruments, such as in gravitational wave detectors or frequency references, thermally induced fluctuations in the reflective coatings can be a limiting noise source. This noise, known as coating thermal noise, can be reduced by choosing materials with low mechanical loss. Examination of new materials becomes a necessity in order to further minimize the coating thermal noise and thus improve sensitivity of next generation instruments. We present a novel approach to directly me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
3
21
2
Order By: Relevance
“…In contrast, the titania-doped tantala film with a cation ratio of 0.27 shows a marked decrease reaching a value of (2.8 ± 0.3)× 10 −4 which is roughly a reduction of 40% in the loss angle compared to the annealed tantala film. This reduction is comparable to previously reported values for titania-doped tantala with a dopant concentration around 20% grown by ion beam sputtering (IBS) [14][15][16][17][18][19][20][21]. It is relevant to point out that at 600 • C the 0.27 cation ratio titania-doped tantala reaches lower values of the loss angle and the absorption loss at 1064 nm than any of the other films in this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the titania-doped tantala film with a cation ratio of 0.27 shows a marked decrease reaching a value of (2.8 ± 0.3)× 10 −4 which is roughly a reduction of 40% in the loss angle compared to the annealed tantala film. This reduction is comparable to previously reported values for titania-doped tantala with a dopant concentration around 20% grown by ion beam sputtering (IBS) [14][15][16][17][18][19][20][21]. It is relevant to point out that at 600 • C the 0.27 cation ratio titania-doped tantala reaches lower values of the loss angle and the absorption loss at 1064 nm than any of the other films in this study.…”
Section: Resultssupporting
confidence: 90%
“…In particular, for the tantala film, the decrease in absorption can be associated with an increase of around 8% in the lattice oxygen proportion as determined by XPS (see Appendix). In fact, in the current state-of-the-art coatings for gravitational wave interferometers, the absorption loss was reduced from 0.7 ppm to 0.25 ppm when the tantala layers of the mirrors were replaced by titania-doped tantala [20]. Dopant cation ratio and annealing also have a profound impact in the mechanical loss of the coatings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal friction of the coatings used in the Advanced LIGO GW detectors have been estimated from measurements made using these techniques, and the loss of the complete mirror stack has been calculated to be roughly 1x10 -4 15 . This value has been roughly verified through direct measurements of S CBTN in laboratory interferometers 28,29 . It has been found that this mechanical loss is dominated by the tantala layers, and the interfaces do not contribute significantly to the loss 22 .…”
Section: Mirror Film Structure and Optical Considerationssupporting
confidence: 52%
“…We calculate this noise assuming the residual pressure in the arms equal to 3 nTorr and is dominated by hydrogen. Thermal noises come from the thermal heat flows and Brownian motion of atoms in the substrate [46] and coating of the mirrors [16,47]. The level of classical noises at 3 kHz is ≈ 5 × 10 −25 strain/ √ Hz.…”
Section: A Ligo-hf Detectormentioning
confidence: 99%